Inflammatory Patterns in Upper Airway Disease in the Same Geographical Area may Change over Time. Issue 5 (September 2013) - Katotomichelakis, Michael; Tantilipikorn, Pongsakorn; Holtappels, Gabriele; De Ruyck, Natalie; Feng, Lan; Van Zele, Thibaut; Muangsomboon, Soranart; Jareonchasri, Perapun; Bunnag, Chaweewan; Danielides, Vassilios; Cuvelier, Claude A.; Hellings, Peter W.; et al.
Background: Inflammatory patterns of nasal polyps (NPs) may vary. Changes over time have not been investigated so far. This study was designed to evaluate the inflammatory patterns of NPs in Thailand at two time points 12 years apart, explore differences in Staphylococcus aureus (SA) mucosal carriage rates over time, and the latter's relationship with the inflammatory patterns. Methods: Formalin-fixed nasal tissue was obtained from 89 (47 in 1999 and 42 in 2011) patients suffering from chronic rhinosinusitis with NPs (CRSwNPs). Tissues were evaluated for eosinophils, neutrophils, IgE + cells, IgE and macrophage mannose receptors, interleukin (IL)-5 and IL-17 cytokine profile, and the presence of SA, using automated immunohistochemistry and peptide nucleic acid–fluorescence in situ hybridization. Results: We found a significant increase in the absolute values of eosinophils and IgE + cells in the 2011 CRSwNP tissue series compared with 1999 and a significant but smaller increase in neutrophils. Semiquantitative evaluation revealed significantly higher mean values of positive cells for all studied inflammatory markers in the 2011 group of patients, except for the high-affinity IgE receptor. This "eosinophilic shift" of inflammation was accompanied by higher SA carriage, as well as higher frequencies of SA invasion (54.8% versus 10.6%; p < 0.001) in the 2011 compared with 1999 subjects. Patients with asthma were more likely to have higher SA carriage rates compared with nonasthmatic patients. Conclusion: There was a shift from predominantly neutrophilic to eosinophilic CRSwNPs in Thai patients within 12 years, with an increase in various inflammatory markers including IgE, which is associated with an increase in intramucosal presence of SA.